مدى تأثير استخدام تقنية الواقع الافتراضي على بعض المتغيرات الفسيولوجية لدى لاعبي جري المسافات الطويلة - الذنيبات، بكر سليمان محمد (جامعة مؤتة, 2023)
هدفت هذه الدراسة للتعرف على مدى تأثير استخدام تقنية الواقع الافتراضي على بعض المتغيرات الفسيولوجية، كما هدفت الدراسة للتعرف على الفروق الإحصائية لأثر استخدام تقنية الواقع الافتراضي على المتغيرات قيد الدراسة، حيث تكون مجتمع الدراسة من (20) لاعبا من لاعبي (جري المسافات الطويلة) واشتملت عينة الدراسة على (9) لاعبين من لاعبي (جري المسافات الطويلة) في النشاط الرياضي في جامعة مؤتة. واستخدم الباحث المنهج الشبه التجريبي بخطواته وإجراءاته العلمية نظرا لتناسبه مع طبيعة هذه الدراسة، وأظهرت نتائج الدراسة أن للواقع الافتراضي (Virtual Reality (VR باستخدام نظارات ثلاثية الأبعاد تأثير واضح على متغيري الدراسة (معدل ضربات القلب (HR) Heart rate، إدراك الجهد (Rated Perceived Exertion (RPE)) على مختلف الشدد (60 واط، 90 واط، 120 واط، 150 واط)، حيث أظهرت نتائج الدراسة أن للواقع الافتراضي (Virtual Reality (VR تأثير دالا إحصائيا لشدة (120 واط) على متغير (معدل ضربات القلب (Heart rate (HR)، كما أظهرت نتائج الدراسة أيضا إن للواقع الافتراضي (Virtual Reality (VR تأثيرا دالا إحصائيا لشدة (150 واط) على متغير (إدراك الجهد (Rated Perceived Exertion (RPE) كما أوصت الدراسة بان تحتوي مختبرات الجهد البدني على غرف متخصصة بالواقع الافتراضي، وأوصت أيضا بإجراء دراسات على الواقع الافتراضي تشمل متغيرات فسيولوجية أخرى مثل (الاكتيك، والجلوكوز، هرون الأندرفين والدوبامين). This study aimed to identify the impact of the use of virtual reality (VR) technology on some physiological variables, and the study aimed to find-out the statistical differences of the impact of the use of virtual reality technology on the variables under study The population of the study consists of (20) players (long distance running). and the sample of the study included (9) players from the players (running long distances) in Sports Activity Center at Mutah University. The researcher used the quasi-experimental approach with its scientific steps and procedures due to its suitability with the nature of this study. The results of the study showed that VR, using three-dimensional glasses, has a clear effect on the two study variables (Heart rate (HR) and (Rated Perceived Exertion (RPE)) on various stress levels (60 watts, 90 watts, 120 watts), and 150 watts), where the results of the study showed that VR has a statistically significant effect of 120 watts on the heart rate (HR) variable. The results of the study also showed that VRity has a statistically significant effect (150 W) on the variable of (RPE). The study recommended that physical laboratories should contain specialized rooms equipped with VR, and it recommended that studies should be run on VR in relation to physiological variables such as Actic, Glucose, Endrophins and Dopamine).
Keywords: الفسيولوجيا الرياضية -- الجهد المدرك -- جري المسافات الطويلة -- اللاعبون الرياضيون -- جامعة مؤتة